Центральний державний архів зарубіжної україніки: перші кроки - Лихолоб, Н. (Архіви України, 2008)
The information deals with the priority developments and major objectives of the new Central State Archives of Archival Ucrainica Abroad. It contains analysis of the documents relating to Ukrainian emigration, acquired from organizations and natural persons.